Cdan1 Is Essential for Primitive Erythropoiesis - Noy-Lotan, Sharon; Dgany, Orly; Marcoux, Nathaly; Atkins, Ayelet; Kupfer, Gary M.; Bosques, Linette; Gottschalk, Christine; Steinberg-Shemer, Orna; Motro, Benny; Tamary, Hannah (Frontiers in Physiology, 2021)
Congenital dyserythropoietic anemia type I (CDA I) is an autosomal recessive disease characterized by moderate to severe macrocytic anemia and pathognomonic morphologic abnormalities of the erythroid precursors, including spongy heterochromatin. The disease is mainly caused by mutations in CDAN1 (encoding for Codanin-1). No patients with homozygous null type mutations have been described, and mouse null mutants die during early embryogenesis prior to the initiation of erythropoiesis. The cellular functions of Codanin-1 and the erythroid specificity of the phenotype remain elusive. To investigate the role of Codanin-1 in erythropoiesis, we crossed mice carrying the Cdan1 floxed allele (Cdanfl/fl) with mice expressing Cre-recombinase under regulation of the erythropoietin receptor promoter (ErGFPcre). The resulting CdanΔEry transgenic embryos died at mid-gestation (E12.5-E13.5) from severe anemia, with very low numbers of circulating erythroblast. Transmission electron microscopy studies of primitive erythroblasts (E9.5) revealed the pathognomonic spongy heterochromatin. The morphology of CdanΔEry primitive erythroblasts demonstrated progressive development of dyserythropoiesis. Annexin V staining showed increases in both early and late-apoptotic erythroblasts compared to controls. Flow cytometry studies using the erythroid-specific cell-surface markers CD71 and Ter119 demonstrated that CdanΔEry erythroid progenitors do not undergo the semi-synchronous maturation characteristic of primitive erythroblasts. Gene expression studies aimed to evaluate the effect of Cdan1 depletion on erythropoiesis revealed a delay of ζ to α globin switch compared to controls. We also found increased expression of Gata2, Pu.1, and Runx1, which are known to inhibit terminal erythroid differentiation. Consistent with this data, our zebrafish model showed increased gata2 expression upon cdan1 knockdown. In summary, we demonstrated for the first time that Cdan1 is required for primitive erythropoiesis, while providing two experimental models for studying the role of Codanin-1 in erythropoiesis and in the pathogenesis of CDA type I.